Consumer satisfaction and loyalty in private‐label food stores. Issue 5 (2014) - ,; ,; ,; ,
Abstract : Purpose – This study aims to determine which factors underlie the store attributes that contribute to a particular food store image. Furthermore, heightened recent attention to private labels in the food retailing industry creates the need to assess whether the factors vary, depending on customers' brand proneness and their impact on key marketing performance variables (satisfaction, attitudinal loyalty, behavioural loyalty).Design/methodology/approach – The proposed analysis features 211 questionnaires out of a sample of 391 consumers surveys gathered in four different store formats; 137 of which were completed by consumers who admitting being private label prone, and 74 pertaining to consumers who considered themselves national brand prone. The underlying food store factors were identified using factorial analysis of principal components, and their influence on consumers' satisfaction and loyalty was evaluated with linear parametric regression models.Findings – Store attributes related to providing sufficiently convenient purchasing experiences and a special atmosphere are most important for private label brand‐prone consumers and enhance their satisfaction, attitudinal loyalty and behavioural loyalty. For national brand‐prone consumers, attributes related to quality are more important for enhancing marketing performance variables.Research limitations/implications – The results enable a clear identification of food store factors that vary with the consumer segment being considered (private label prone consumers vs. national brand prone), as well as their differential impacts on key marketing performance variables.Practical implications – To appeal to private label‐prone consumers, food retailers should put particular emphasis on the attributes of the store itself, especially those that enhance convenience and the pleasantness of the store atmosphere. To attract national brand‐prone consumers, they primarily need to highlight aspects related to quality.Originality/value – This research emphasises the importance of building competitive strategies in food retailing based on: an increased knowledge about the attributes and factors that food consumers value more highly; and brand type preferences.